Drug-induced interstitial lung disease in the treatment of malignant lymphoma as a potential diagnostic marker: a comparison of serum Krebs von Lungen-6 and thymus and activation-regulated chemokine/CC chemokine ligand 17 - Yamane H; Ochi N; Nagasaki Y; Yamagishi T; Honda Y; Nakagawa N; Takeyama M; Nakanishi H; Takigawa N (Dove Medical Press, 2018)
Hiromichi Yamane, Nobuaki Ochi, Yasunari Nagasaki, Tomoko Yamagishi, Yoshihiro Honda, Nozomu Nakagawa, Masami Takeyama, Hidekazu Nakanishi, Nagio Takigawa Department of General Internal Medicine 4, Kawasaki Medical School, Okayama, Japan Purpose: Cure-oriented treatment of malignant lymphoma (ML) is possible even in an advanced stage; however, the progression of drug-induced interstitial lung disease (DILD) sometimes accounts for poor clinical outcomes. This study aims to assess the incidence and clinical characteristics of DILD among patients with ML and compares the serum level of Krebs von den Lungen-6 (KL-6) with that of circulating thymus and activation-regulated chemokine (TARC)/CC chemokine ligand 17 (CCL17) as a diagnostic biomarker for DILD.Patients and methods: Between July 2011 and August 2016, we enrolled 36 patients with ML who were undergoing systemic chemotherapy at our hospital. Then, we evaluated the serum concentration of KL-6 and TARC/CCL17 by a sandwich-type electrochemiluminescence immunoassay and enzyme-linked immunosorbent assay, respectively.Results: DILD developed in 22.2% of patients with ML. All patients recovered immediately after the discontinuation of causative drug and/or glucocorticoid therapy. Although the sensitivity of both TARC/CCL17 and KL-6 was almost equal, the mean concentration of serum KL-6 after the progression of interstitial lung disease was significantly higher than that before progression.Conclusion: DILD developed in patients who were treated with first-line rituximab combined regimen. Remarkably, TARC/CCL17 and KL-6 seemed approximately equal as a predictive biomarkers for DILD; however, KL-6 was more specific than TARC/CCL17. Keywords: malignant lymphoma, drug-induced interstitial lung disease, KL-6, TARC/CCL17, biomarker